2006
DOI: 10.1590/s1516-44462006000500004
|View full text |Cite
|
Sign up to set email alerts
|

Autismo: neuroimagem

Abstract: A b s t r a c t Autism is a neurodevelopmental disorder with a range of clinical presentations. These presentations vary from mild to severe and are referred to as autism spectrum disorders. The most common clinical sign of autism spectrum disorders is social interaction impairment, which is associated with verbal and non-verbal communication deficits and stereotyped and repetitive behaviors. Thanks to recent brain imaging studies, scientists are getting a better idea of the neural circuits involved in autism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
17

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 64 publications
0
2
0
17
Order By: Relevance
“…More specifically, the pSTS is known to differ structurally between individuals with and without ASD [Boddaert & Zilbovicius, ; Boddaert, Chabane, Gervais, et al, ; Boddaert et al, ; Brunelle, Boddaert, & Zilbovicius, ; Levitt et al, ] in both gray matter volume [Boddaert, Chabane, Gervais, et al, ], gyrations [Levitt et al, ], and white matter connectivity [Boddaert, Chabane, Gervais, et al, ; Conturo et al, ; Lange et al, ; Lee et al, ]. Posterior STS also showed differential activation patterns with audiovisual speech stimuli and complex sounds in individuals with ASD relative to their TD peers [Boddaert & Zilbovicius, ; Brunelle et al, ; Boddaert et al, ; Boddaert, Chabane, Belin, et al, ; Pelphrey & Carter, ; Redcay & Courchesne, ; Zilbovicius et al, ; Zilbovicius, Meresse, & Boddaert, ; Zilbovicius, Meresse, Chabane, et al, ]. Finally, pSTS has been functionally linked to a wide array of other cognitive processes known to be impaired in ASD, including, but not limited to, processing of social stimuli, biological motion, face processing, and theory of mind [for review, see Hein & Knight, ].…”
Section: Examination Of Autism Traits In the General Populationmentioning
confidence: 99%
“…More specifically, the pSTS is known to differ structurally between individuals with and without ASD [Boddaert & Zilbovicius, ; Boddaert, Chabane, Gervais, et al, ; Boddaert et al, ; Brunelle, Boddaert, & Zilbovicius, ; Levitt et al, ] in both gray matter volume [Boddaert, Chabane, Gervais, et al, ], gyrations [Levitt et al, ], and white matter connectivity [Boddaert, Chabane, Gervais, et al, ; Conturo et al, ; Lange et al, ; Lee et al, ]. Posterior STS also showed differential activation patterns with audiovisual speech stimuli and complex sounds in individuals with ASD relative to their TD peers [Boddaert & Zilbovicius, ; Brunelle et al, ; Boddaert et al, ; Boddaert, Chabane, Belin, et al, ; Pelphrey & Carter, ; Redcay & Courchesne, ; Zilbovicius et al, ; Zilbovicius, Meresse, & Boddaert, ; Zilbovicius, Meresse, Chabane, et al, ]. Finally, pSTS has been functionally linked to a wide array of other cognitive processes known to be impaired in ASD, including, but not limited to, processing of social stimuli, biological motion, face processing, and theory of mind [for review, see Hein & Knight, ].…”
Section: Examination Of Autism Traits In the General Populationmentioning
confidence: 99%
“…This hypoperfusion was presumed to impair the transfer of auditory information and social perception (eye contact and facial expression), relational difficulties characteristic of autistic children. Ulterior studies, which undertook a neurofunctional perspective, reported diminished responses to auditory stimuli (Gomot et al, 2006) and visual stimuli (Bölte et al, 2008), along with hemodynamic modifications (Zilbovicius et al, 2006). The autistic brain reacts faintly to stimuli variations, a fact which agrees with some of the basic diagnosis criteria, such as a reduced interest for all surroundings, resistance to change and stereotypical activities.…”
Section: Wwwintechopencommentioning
confidence: 68%
“…Independente da causa, reconhece-se alterações do sistema nervoso central (SNC) em crianças com TEA, mais precisamente nas áreas cerebrais como hipocampo, amígdalas, corpo caloso, maturação do córtex cerebral frontal, e desenvolvimento irregular dos neurônios do sistema límbico (ZILBOVICIUS, 2006). Outra evidência seria relacionada à circunferência craniana cerebral de crianças com TEA, que ao nascer podem apresentar valores inferiores à média.…”
Section: Referencial Teóricounclassified